Density Functional Calculations Recent Progresses of Theory and Application - Yang, Gang (IntechOpen, 2018)
Density functional theory (DFT) ranks as the most widely used quantum mechanical method and plays an increasingly larger role in a number of disciplines such as chemistry, physics, material, biology, and pharmacy. DFT has long been used to complement experimental investigations, while now it is also regarded as an indispensable and powerful tool for researchers of different fields. This book is divided into five sections that include original chapters written by experts in their fields: "Method Development and Validation," "Spectra and Thermodynamics," "Catalysis and Mechanism," "Material and Molecular Design," and "Multidisciplinary Integration." I would like to express my sincere gratitude to all contributors and recommend this book to both beginners and experienced researchers.